2020
DOI: 10.1371/journal.pone.0229570
|View full text |Cite
|
Sign up to set email alerts
|

Herpes simplex virus type 1 inflammasome activation in proinflammatory human macrophages is dependent on NLRP3, ASC, and caspase-1

Abstract: The proinflammatory cytokines interleukin (IL)-1β and IL-18 are products of activation of the inflammasome, an innate sensing system, and important in the pathogenesis of herpes simplex virus type 1 (HSV-1). The release of IL-18 and IL-1β from monocytes/macrophages is critical for protection from HSV-1 based on animal models of encephalitis and genital infection, yet if and how HSV-1 activates inflammasomes in human macrophages is unknown. To investigate this, we utilized both primary human monocyte derived ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 56 publications
(81 reference statements)
1
29
0
Order By: Relevance
“…Furthermore, HSV-1 induced transcription of molecular pathways that promote fibrotic in IPF [ 99 ]. Supporting the previous study, Karaba et al found HSV-1 activates canonical and non-canonical NLRP3 inflammasome pathways to lead to the release of IL-1β [ 100 ]. In a bleomycin-induced mouse model, scutellarin suppressed excessive EMT and inflammation via NF-κβ/NLRP3 pathway [ 101 ].…”
Section: Potential Mechanism Of Virus Infection-induced Damage That Associated With the Nlrp3 Inflammasomesupporting
confidence: 69%
“…Furthermore, HSV-1 induced transcription of molecular pathways that promote fibrotic in IPF [ 99 ]. Supporting the previous study, Karaba et al found HSV-1 activates canonical and non-canonical NLRP3 inflammasome pathways to lead to the release of IL-1β [ 100 ]. In a bleomycin-induced mouse model, scutellarin suppressed excessive EMT and inflammation via NF-κβ/NLRP3 pathway [ 101 ].…”
Section: Potential Mechanism Of Virus Infection-induced Damage That Associated With the Nlrp3 Inflammasomesupporting
confidence: 69%
“…IFI16 interacts directly with interferon-β, inducing DNA to recruit IRF3 and NF-κB for the transcription of genes involved in inflammatory response. In a recent publication, HSV-1 was shown to also activate the inflammatory response via the nucleotide-binding domain and leucine-rich repeat-containing receptor 3 (NLRP3) [ 44 ].…”
Section: Herpes Simplex Virus and The Immune Systemmentioning
confidence: 99%
“…Human monocytes can be obtained from freshly isolated PBMCs according to established protocols [ 12 , 80 ] and differentiated into human monocyte-derived macrophages (hMDMs). To this purpose, different approaches have been developed where different stimuli can be used in order to obtain a specific macrophage polarization [ 12 , 81 , 82 ]. For example, M-CSF-differentiated hMDMs treated with LPS/IFNγ or IL-4, become polarized toward the M1 or M2 phenotype, respectively [ 83 , 84 ].…”
Section: Cell Models To Study Nlrp3 Inflammasome Biologymentioning
confidence: 99%